Pengaruh Ukuran Perusahaan, Profitabilitas Dan Leverage Terhadap Manajemen Laba Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Rani Mahmudah; Endang Kartini; Sofiati Wardah (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This study aims to determine the effect of company size, profitability and leverage on profit management in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. This type of research is associative research with a quantitative approach that aims to determine the relationship between two or more variables. The type of data in this study uses secondary data where the data is obtained from annual financial reports. The sampling technique uses purposive sampling method. The samples used in this study amounted to 21 banking companies multiplied by 4 years, namely 84 samples. In this study, the data analysis model used was multiple linear regression using SPSS 26 software. The results of this study concluded that partially firm size and leverage have no effect on earnings management. Meanwhile, profitability has a significant and significant effect on earnings management in food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2022 period.